«Recull de contes valencians»: una aproximació al conte de postguerra - Gregori, Carme (Caplletra. Revista Internacional de Filologia, 2015)
Considering Joan Fuster's Recull de contes valencians published in 1958, this paper analyses the short story situation during the franquism. On the one hand, It takes into account the precedents that appeared between 1938 and 1958 and on the other hand, the authors and the compilation.